Theoretical foundations of economic security as part of the economic law of Ukraine - Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The theory of economic security as an element of economic law - the definition of the role and place of economic relations in the economic security on the basis of existing regulations in the field of commercial law and establish mechanisms to ensure economic security through legal mechanisms. In the theory of economic security as an element of economic law includes such categories as: objects, subjects, subject regulatory mechanism of economic security through legal mechanisms. The objects are the economic security of the economic system as a whole and its various components: natural resources, manufacturing and non-productive assets, property, financial resources, economic structures, family, an individual like. The subjects are the economic security of the state and its institutions (ministries, departments, tax and customs authorities, exchanges, funds and insurance companies), as well as enterprises, institutions and organizations in both the public and private sector. Economic security is inherent integral character because it is a collaborative effort of the nation, which is manifested through the actions of all branches of government at all levels (from local to nationwide), existing state capability, NGOs and individuals. The subject of the state in economic security is a monitoring factors that undermine social stability of the economic system of the state in the short and long term, ie identifying and predicting threats; developing specific measures implementations of policy and institutional reforms that eliminate or mitigate the harmful effects of identified factors and threats within a single economic reform program of the country.